Masculinity and Men’s Health Attitudes Toward Consideration of Weight-Loss Surgery - (:unkn) unknown (My University, 2022)
The rise in obesity across the United States has led to greater educational outreach, considerable research, and medical interventions aimed at decreasing the rate of obesity-related health diseases. But are these interventions reaching everyone? Despite men and women having equivalent rates of obesity, only 20% of weight-loss surgery patients are men. While men have an average life expectancy that is 5 years less than women and are twice as likely than women to have heart disease, men also underutilize healthcare services. Given these factors, this research explored men’s health beliefs, conformity to male norms, and receptivity to weight-loss surgery. This study examined whether a masculine self-identity moderated men’s health beliefs in predicting receptivity to weight-loss surgery. A sample of men who self-reported a BMI of ≥35 were surveyed. This study used a modified health belief model to examine the predictive capability of Perceived Severity, Perceived Susceptibility, Benefits, Barriers, Self-Efficacy, Health Value & Importance, Consideration of Future Consequences, and Appearance and our outcome variable of Consideration of WLS. Furthermore, this study examined whether five of the aforementioned variables were moderated by Masculine Self-Identity. The results showed that masculinity significantly changed the relationship between health beliefs as measured by Barriers, Perceived Susceptibility, Health Value & Importance, and Perceived Severity and Consideration of WLS. Furthermore, the endorsement of a Masculine Self-Identity had the greatest interaction effects with predictors Health Value & Importance and Perceived Susceptibility and our outcome Consideration of WLS. These findings, which support literature that health-behaviors are influenced by masculinity, suggest masculinity plays a role in Consideration of WLS.
Keywords: Bariatric; Health; Health Beliefs; Masculinity; Obesity; Weight-Loss Surgery